The burden of chronic rhinosinusitis and its effect on quality of life among patients re-attending an otolaryngology clinic in south western Uganda - Nyaiteera, Victoria (BMC Ear Nose Throat Disord, 2018)
BACKGROUND: Worldwide, the burden of chronic rhinosinusitis (CRS) is variable, but not known in Uganda. CRS has significant negative impact on quality of life (QOL) and as such QOL scores should guide adjustments in treatment strategies. However, most of these studies have been done in the west. Our hypothesis was that QOL scores of the majority of CRS patients in low- to- middle income countries are poorer than those among patients without CRS. The aim of this study was to determine the burden of CRS among patients re-attending the Otolaryngology clinic and whether CRS is related to poor QOL. METHODS: A cross sectional study was conducted at Mbarara Regional Referral Hospital Otolaryngology clinic. One hundred and twenty-six adult re-attendees were consecutively recruited. Data was collected using a structured questionnaire and the Sinonasal Outcome Test 22 (SNOT 22) questionnaire measured QOL. RESULTS: The proportion of re-attendees with CRS was 39.0% (95% CI 30–48%). Majority of CRS patients had poor quality of life scores compared to non-CRS (88% versus 20% p < 01). The poor quality of life scores on the SNOT 22 were almost solely as a result of the functional, physical and psychological aspects unique to CRS. CONCLUSIONS: CRS is highly prevalent among re-attendees of an Otolaryngology clinic at a hospital in resource limited settings and has a significant negative impact on the QOL of these patients.